The 2nd Berlin BedRest Study: protocol and implementation - Belavý, D L; Bock, O; Börst, H; Armbrecht, G; Gast, U; Degner, C; Beller, G; Soll, H; Salanova, M; Habazettl, H; Heer, M; de Haan, A; et al. (Journal of musculoskeletal & neuronal interactions, 2010)
Long-term bed-rest is used to simulate the effect of spaceflight on the human body and test different kinds of countermeasures. The 2nd Berlin BedRest Study (BBR2-2) tested the efficacy of whole-body vibration in addition to high-load resisitance exercise in preventing bone loss during bed-rest. Here we present the protocol of the study and discuss its implementation. Twenty-four male subjects underwent 60-days of six-degree head down tilt bed-rest and were randomised to an inactive control group (CTR), a high-load resistive exercise group (RE) or a high-load resistive exercise with whole-body vibration group (RVE). Subsequent to events in the course of the study (e.g. subject withdrawal), 9 subjects participated in the CTR-group, 7 in the RVE-group and 8 (7 beyond bed-rest day-30) in the RE-group. Fluid intake, urine output and axiallary temperature increased during bed-rest (p < .0001), though similarly in all groups (p > or = .17). Body weight changes differed between groups (p < .0001) with decreases in the CTR-group, marginal decreases in the RE-group and the RVE-group displaying significant decreases in body-weight beyond bed-rest day-51 only. In light of events and experiences of the current study, recommendations on various aspects of bed-rest methodology are also discussed.